The electric conductivities of aqueous solutions of rubidium and cesium cyclohexylsulfamates, potassium acesulfame and sodium saccharin - Rudan Tasič, Darja (Acta chimica slovenica, 2006)
The electric conductivities of aqueous solutions of rubidium and cesium salts of cyclohexylsulfamic acid, potassium acesulfame and sodium saccharin were measured from 5 °C to 35 °C (in steps of 5 °C) in the concentration range 0.0003 < c/mol dm-3 < 0.01. Data analysis based on the chemical model of electroyte solutions yielded the limiting molar conductivity .. and the association constant KA. Using the known data of the limiting conductivities of rubidium, cesium, sodium and potassium ions the limiting conductivities of the cyclohexylsulfamate, accesulfame and saccharin ions were evaluated. Total dissociation of the investigated salts in water and negligible hydration of anions are evident.
Keywords: cikloheksilsulfamati; električna prevodnost; elektroliti; fizikalna kemija; modeli; molska prevodnost; raztopine; saharin; umetna sladila